Teaching Life Lessons: When Millennials Fail - Ramirez, Jeffery; Isaacson, Janalee; Smith, Deborah; Senger, Brenda (Building Healthy Academic Communities Journal, 2018)
Background: Students who fail may face feelings of diminished self-perception, decreased sense of achievement, and experience negative emotions or moods such as: guilt, embarrassment, thoughts of reoccurring failure, feeling of letting others down or disappointing teachers and parents. Aim: This paper is to discusses the topic of failure and providing thoughts and reflections on the topic. The authors believe that faculty can help students learn to fail and also maintain their self-worth and dignity. Helping students learn from these failures and promoting resilience and humility when faced with life adversities may be one of the best lifelong lessons faculty can teach. Results: Failure is never an easy experience. When a student is faced with failure, it is critical for faculty to help the student find the positives of the experience. This as an opportunity to promote personal growth and character development. Educators are in a precarious position because learning outcomes are based on successful performance and failure can be looked upon negatively for faculty. Conclusions: Faculty are perfectly positioned to help reframe failure for students struggling in college and help them find their true passion in life. College is a transformative experience, a time for self-discovery and finding one’s true identity. It is a time to learn life lessons and how to manage adversity facilitating strong, emotionally healthy, driven men and women of future generations.